Vaborbactam: Spectrum of Beta-Lactamase Inhibition and Impact of Resistance Mechanisms on Activity in Enterobacteriaceae - Lomovskaya, Olga (Antimicrob Agents Chemother, 2017)
Vaborbactam (formerly RPX7009) is a new beta-lactamase inhibitor based on a cyclic boronic acid pharmacophore. The spectrum of beta-lactamase inhibition by vaborbactam and the impact of bacterial efflux and permeability on its activity were determined using a panel of strains with beta-lactamases cloned from various classes and a panel of Klebsiella pneumoniae carbapenemase 3 (KPC-3)-producing isogenic strains with various combinations of efflux and porin mutations. Vaborbactam is a potent inhibitor of class A carbapenemases, such as KPC, as well as an inhibitor of other class A (CTX-M, SHV, TEM) and class C (P99, MIR, FOX) beta-lactamases. Vaborbactam does not inhibit class D or class B carbapenemases. When combined with meropenem, vaborbactam had the highest potency compared to the potencies of vaborbactam in combination with other antibiotics against strains producing the KPC beta-lactamase. Consistent with broad-spectrum beta-lactamase inhibition, vaborbactam reduced the meropenem MICs for engineered isogenic strains of K. pneumoniae with increased meropenem MICs due to a combination of extended-spectrum beta-lactamase production, class C beta-lactamase production, and reduced permeability due to porin mutations. Vaborbactam crosses the outer membrane of K. pneumoniae using both OmpK35 and OmpK36, but OmpK36 is the preferred porin. Efflux by the multidrug resistance efflux pump AcrAB-TolC had a minimal impact on vaborbactam activity. Investigation of the vaborbactam concentration necessary for restoration of meropenem potency showed that vaborbactam at 8 μg/ml results in meropenem MICs of ≤2 μg/ml in the most resistant engineered strains containing multiple mutations. Vaborbactam is a highly active beta-lactamase inhibitor that restores the activity of meropenem and other beta-lactam antibiotics in beta-lactamase-producing bacteria, particularly KPC-producing carbapenem-resistant Enterobacteriaceae.